2013
DOI: 10.1039/c2fd20133j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hot carriers on catalytic reaction; Pt nanoparticles on GaN substrates under light irradiation

Abstract: We report the hot carrier-driven catalytic activity of two-dimensional arrays of Pt nanoparticles on GaN substrate under light irradiation. In order to elucidate the effect of a hot carrier in a catalytic chemical reaction, the CO oxidation reaction was carried out on Pt nanoparticles on p- and n-type GaN under light irradiation. Metal catalysts composed of Pt nanoparticles were prepared using two different preparation methods: the one-pot polyol reduction and are plasma deposition methods. Under light irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The shorter travel length of hot electrons lowers the consumption of kinetic energy when the hot electrons reach the metal/adsorbate interface, leaving a larger fraction of energy to facilitate the electron injection from the metal surface to adsorbate species and/or to promote the direct interaction between the hot electrons with the adsorbate species. 25,26 The effect of shorter travel length of hot electrons in smaller metal nanoparticles and signicant "reverse Coulomb blockade effect" on the surface of smaller metal nanoparticles can synergistically benet surface chemical reactions, resulting in the observation of faster reaction kinetics on smaller metal nanoparticles. Fig.…”
Section: Quantum-sized Metal Nanoparticlesmentioning
confidence: 99%
“…The shorter travel length of hot electrons lowers the consumption of kinetic energy when the hot electrons reach the metal/adsorbate interface, leaving a larger fraction of energy to facilitate the electron injection from the metal surface to adsorbate species and/or to promote the direct interaction between the hot electrons with the adsorbate species. 25,26 The effect of shorter travel length of hot electrons in smaller metal nanoparticles and signicant "reverse Coulomb blockade effect" on the surface of smaller metal nanoparticles can synergistically benet surface chemical reactions, resulting in the observation of faster reaction kinetics on smaller metal nanoparticles. Fig.…”
Section: Quantum-sized Metal Nanoparticlesmentioning
confidence: 99%
“…Upon light illumination, the photon-induced charge transfer of the excited carriers between the metal particle and semiconductor support can provide a steady-state potential shift of the active surfaces, resulting in different thermal catalytic reactivity. 62 For instance, choosing n- or p-type semiconductors as the support can determine the type of contact, either Schottky or ohmic, which additionally dictate the charge transfer at the interface. 63 Using Pt supported on p- or n-GaN as a model, the groups of Lercher and Stutzmann studied the variation in the electronic structure of Pt.…”
Section: Outlook For Other Innovative Catalysismentioning
confidence: 99%
“… 64 Its resultant catalysis was also altered; higher activity for thermal CO oxidation over Pt/n-GaN than over Pt/p-GaN was observed. 62 The electride is another non-conventional support, where, according to the research of Hosono's group, by the electron donation from the support to the metal, the catalyst can not only lower the activation energy of ammonia synthesis over a Ru catalyst, but also suppress the poisoning of the Ru surface caused by H adatoms. 65 The application of such novel materials to the support would open a new frontier of supported metal catalysis.…”
Section: Outlook For Other Innovative Catalysismentioning
confidence: 99%
“…Kim et al reported that the change in catalytic activity for CO oxidation on Au/CeO 2 or Pt/GaN catalysts under light irradiation decreased as the size of the Au or Pt nanoparticles increased because of the length of the mean free path of the metal. 24,26 Lee et al found that smaller Pt nanoparticles lead to higher chemicurrent yield (i.e. the number of hot electrons detected per molecule of reaction product formed on the Au/ TiO 2 nanodiode surface) during hydrogen oxidation, which is associated with the shorter travel length for the hot electrons, compared with their inelastic mean free path.…”
mentioning
confidence: 99%
“…[20][21][22][23] In addition, there are some studies that show the inuence of hot electrons from the oxide or semiconductor support on the catalytic activity of metal catalysts when under light irradiation. [24][25][26] To understand the intrinsic relation between catalytic activity and hot electron ows generated across metal-oxide interfaces, the design of a fresh catalyst model is important. 27 In previous studies, the active site was the metal, which is inu-enced by hot electrons from an oxide or a semiconductor.…”
mentioning
confidence: 99%